Aplikasi Inventaris Berbasis Komputer Workshop Alat Berat Politeknik Negeri Padang - Andriyanto Andriyanto; Atikah Ardi; Dian Wahyu; Hanif Hanif; Nofriyandi R; Dimas Satrio Laksono Nugroho (AEEJ : Journal of Automotive Engineering and Vocational Education, 2023)
The purpose of this research is to design a Computer-Based Inventory application of equipment in the Heavy Equipment Workshop of Padang State Polytechnic. Historically, the borrowing, returning, utility, and tool data recording have been manual processes involving a substantial amount of paperwork, often leading to errors in item placement, difficulties in accessing information, and the risk of data loss. This application not only provides a centralized platform for recording and monitoring inventory but also facilitates real-time information access. With this technology, workshops can avoid shortages or excesses of items, enhance the efficiency of heavy equipment utilization, and optimize maintenance cycles. The methodology employed in developing this application is the Waterfall Development Method. The research outcome is a computer-based application using Visual Basic and SQL Server Database. Penelitian ini bertujuan untuk merancang aplikasi Inventaris Berbasis Komputer peralatan di Workshop Alat Berat Politeknik Negeri Padang. Selama ini peminjaman, pengembalian, Utility, dan pendataan tools dilakukan secara manual menggunakan kertas sehingga memakan waktu dan kertas yang banyak, seringkali mengakibatkan kesalahan peletakan barang, kesulitan akses informasi, dan risiko kehilangan data. Aplikasi inventaris workshop alat berat ini tidak hanya menyediakan platform terpusat untuk mencatat dan memantau inventaris, tetapi juga memberikan kemudahan dalam mengakses informasi secara real-time. Metode yang digunakan pada pembuatan aplikasi ini adalah Metode Research and Development (R&D) dengan model Pengembangan Waterfall. Hasil penelitian ini adalah aplikasi berbasis komputer menggunakan Visual Basic dan SQL Server Database yang dapat digunakan untuk peminjaman dan pengembalian inventaris di workshop alat berat sehingga semua tools dapat terdata dengan baik.